Description and evaluation of a function‐informed and mechanisms‐based framework for treating challenging behavior. Issue 4 (28th June 2022) - Lambert, Joseph M.; Copeland, Bailey A.; Paranczak, Jessica L.; Macdonald, M. Janey; Torelli, Jessica N.; Houchins‐Juarez, Nealetta J.
Abstract : Individualization and iterative design are essential components of the assessment and treatment of challenging behavior. Currently, there are few validated frameworks for engaging in iterative processes. Due to the nature of single‐case design, empirically rigorous evaluations of decision‐tree processes are particularly prohibitive. Notwithstanding, evaluations are needed. In this paper we first describe a function‐informed and mechanisms‐based (FIMB) framework for selecting treatment components employed by a university‐based practicum experience designed to expose pre‐service practitioners to a valid treatment process for challenging behavior. Then, we share a completed retrospective consecutive case series across a 6‐year period in which we conducted a technique analysis to identify which procedures were most commonly selected in the practicum, and the impact of those choices on client outcomes. The results suggest that the model can be highly effective for some, but not all, cases. Implications are discussed.